2015
DOI: 10.1097/prs.0000000000001453
|View full text |Cite
|
Sign up to set email alerts
|

Google Glass as an Alternative to Standard Fluoroscopic Visualization for Percutaneous Fixation of Hand Fractures

Abstract: This pilot study investigated the feasibility of Google Glass to assist visualization of fluoroscopic images during percutaneous pinning of hand fractures. Cadavers were used to compare total time to pin each fracture and total number of radiographs per fracture from a mini C-arm. A FluoroScan monitor was used for radiographic visualization compared to projecting the images in the Google Glass display. All outcome measures significantly improved for proximal phalanx fractures (127 versus 86 seconds, p = 0.017;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 1 publication
1
53
0
Order By: Relevance
“…Fifteen of the 34 articles (44%) featuring the use of Google Glass were primary research articles;2 5 8 10 11 15 16 19 21 26 28 31 32 35 36 of these, 12 described either exploratory studies or ‘proof-of-concept’ case studies in clinical settings. In general, all of these studies concluded that Google Glass has the potential to enhance various aspects of surgery, but the majority highlighted functional limitations (eg, limited battery life, insufficient resolution and rudimentary voice control), usability issues (eg, incompatibility with surgical loupes, mismatch between the user's natural line of sight and the position of the display) and privacy concerns as significant barriers to practical clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen of the 34 articles (44%) featuring the use of Google Glass were primary research articles;2 5 8 10 11 15 16 19 21 26 28 31 32 35 36 of these, 12 described either exploratory studies or ‘proof-of-concept’ case studies in clinical settings. In general, all of these studies concluded that Google Glass has the potential to enhance various aspects of surgery, but the majority highlighted functional limitations (eg, limited battery life, insufficient resolution and rudimentary voice control), usability issues (eg, incompatibility with surgical loupes, mismatch between the user's natural line of sight and the position of the display) and privacy concerns as significant barriers to practical clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Unrestricted freedom of motion gave battery-powered wearables a distinct advantage over their wire-connected counterparts, but poor battery life was repeatedly cited as a serious limitation to device usability; when subjected to the heavy usage of continuous video streaming, Google Glass had a reported battery life of 30–40 min,5 10 while GoPro devices required charging after 90 min of continuous recording 39 43. Since these devices were originally developed for the consumer market,1 2 it is not surprising that their designs and capabilities have not been optimised for medical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem may be solved by techniques allowing for simultaneous or in-line visualization of the procedural site and guiding images. [19][20][21][22] Recently introduced OST-HMD headsets can display high resolution images directly in the operator's field of view without obstructing the rest of the procedural scene. 23 24 OST-HMD headsets offer a synchronized assessment of body, image, and action that can confer a significant advantage over traditional display modes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of smart glasses may offer a solution to these problems, enabling the clinician to direct their gaze wherever they like as the images would appear within the smart glasses rather than on computer monitors located somewhere in the clinical room. 8 In turn this may result in procedures being completed faster and safer as the clinician would be able to observe the live radiographic image without looking away from the patient. Additionally, clinicians are able to record the procedure for future teaching purposes.…”
Section: Introductionmentioning
confidence: 99%